KUB Batik Sekar sebagai Model Pemberdayaan Perempuan Berbasis Ekonomi Lokal: Studi Kasus Desa Putat, Grobogan - Mukaromah, Muslikatul; Riyadi, Agus (Kolaborasi Masyarakat, 2025)
Women in rural areas continue to face limited access to education and economic opportunities, which prevents their potential from being fully developed. This study analyzes women’s empowerment through the local economic initiative Kelompok Usaha Bersama (KUB) Batik Sekar in Putat Village, Purwodadi District, Grobogan Regency. A qualitative descriptive design was employed, using interviews, observations, and document analysis involving 20 female participants, local stakeholders, and government representatives. The findings show that the KUB Batik Sekar program enhances women’s skills in batik production, financial management, and marketing, which subsequently led to the formation of five new batik groups. Household income increased, reflected by an average percentage rise compared to the previous year. The empowerment process also strengthened women’s confidence, independence, and decision making roles within both the family and community. The proposed empowerment model emphasizes collaboration between skills training, organizational capacity building, and marketing network support. Although challenges remain, particularly in market competition and infrastructure, government and community support helps sustain the program. These findings demonstrate that women’s involvement in the local economy can improve welfare, drive social transformation, and preserve batik cultural heritage.